Primo New User Interface: Usability Testing and Local Customizations Implemented in Response - Galbreath, Blake Lee; Johnson, Corey; Hvizdak, Erin (Information Technology and Libraries, 2018)
Washington State University was the first library system of its 39-member consortium to migrate to Primo New User Interface. Following this migration, we conducted a usability study in July 2017 to better understand how our users fared when the new user interface deviated significantly from the classic interface. From this study, we learned that users had little difficulty using basic and advanced search, signing into and out of primo, and navigating their account. In other areas, where the difference between the two interfaces was more pronounced, study participants experienced more difficulty. Finally, we present customizations implemented at Washington State University to the design of the interface to help alleviate the observed issues.